Antipsychotic use and associating factors among persons with substance-induced psychosis and first-episode psychotic disorder- A nationwide register-linkage study - Jeyapalan, Jeyaniroshan; Taipale, Heidi; Tanskanen, Antti; Tiihonen, Jari; Mittendorfer-Rutz, Ellenor; Niemelä, Solja (Elsevier, 2026)
Background
Antipsychotic use after first-episode psychotic disorder (FEPD) has been widely studied, but data on substance-induced psychosis (SIP) are lacking.
Objectives
To examine the prevalence and associated factors of antipsychotic use in individuals with incident SIP compared to a matched FEPD cohort.
Methods
From Swedish healthcare registers, 7320 incident SIP cases (2006–2016) were identified and matched 1:1 by age, sex, and year with FEPD cases. The point prevalence of antipsychotic use was assessed biannually from three years before to three years after the incident diagnosis. Associations between any antipsychotic use during one year post-diagnosis and sociodemographic, clinical, and work-related factors were estimated using modified Poisson regression to obtain unadjusted and age- and sex-adjusted risk ratios (RRs) with 95% CIs. This register-based analysis followed RECORD reporting standards.
Results
The point prevalence of antipsychotic use peaked six months after the first psychotic episode (23% in SIP vs 54% in FEPD) and remained approximately stable thereafter (20% vs 50% at three years). During the first year, the cumulative prevalence of any antipsychotic use was 43% in SIP and 73% in FEPD. Among SIP patients, younger age, female sex, non-European origin, and prior psychiatric comorbidity particularly anxiety, depression, ADHD, and personality disorders were the strongest correlates of antipsychotic use. Functional impairment indicators such as long-term sickness absence and disability pension were also associated with increased use. In FEPD, age, depression, autism-spectrum diagnosis, and short-term sickness absence showed similar but weaker patterns. Olanzapine was the most commonly used antipsychotic in both cohorts.
Conclusions
Despite diagnostic definitions describing SIP as transient, a substantial proportion of patients continued antipsychotic treatment beyond the acute phase. These findings emphasise that younger age, psychiatric comorbidity, and psychosocial vulnerability strongly influence prescribing decisions in SIP and highlight the need for evidence-based, subtype-specific treatment guidelines.